2022
DOI: 10.3389/fneur.2022.807145
|View full text |Cite
|
Sign up to set email alerts
|

Hyperdense Artery Sign in Patients With Acute Ischemic Stroke–Automated Detection With Artificial Intelligence-Driven Software

Abstract: BackgroundHyperdense artery sign (HAS) on non-contrast CT (NCCT) can indicate a large vessel occlusion (LVO) in patients with acute ischemic stroke. HAS detection belongs to routine reporting in patients with acute stroke and can help to identify patients in whom LVO is not initially suspected. We sought to evaluate automated HAS detection by commercial software and compared its performance to that of trained physicians against a reference standard.MethodsNon-contrast CT scans from 154 patients with and withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…A recent large AI study, using a historical database of 24214 patients for training and 1453 patients for validation, established a machine learning algorithm and a software (MethinksLVO) [18] capable of rapidly and reliably predicting LVO from NCCT scans with slice thickness 3-to-5 mm. Weyland et al [23] tested a readily available software, Brainomix © (Oxford, UK). Shinohara et al developed [19] and tested [20] an interactive deep learning-assisted identification of HMCAS, on NCCT.…”
Section: Automatic Detection and Segmentation Of The Clotmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent large AI study, using a historical database of 24214 patients for training and 1453 patients for validation, established a machine learning algorithm and a software (MethinksLVO) [18] capable of rapidly and reliably predicting LVO from NCCT scans with slice thickness 3-to-5 mm. Weyland et al [23] tested a readily available software, Brainomix © (Oxford, UK). Shinohara et al developed [19] and tested [20] an interactive deep learning-assisted identification of HMCAS, on NCCT.…”
Section: Automatic Detection and Segmentation Of The Clotmentioning
confidence: 99%
“…A growing number of articles are evaluating AI techniques that analyze the neuroimaging signs of the clot (or thrombus) occluding the arteries in ischemic stroke [13] [14] [15] [16] [17] [18] [19] [20] [21] [22] [23]. No systematic reviews were conducted so far to examine the progress made in developing AI methods that are using clot imaging derived parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Lower clot burden, smaller thrombus length, and more distal thrombus location are predictors of a better clinical and radiologic outcome [ 8 , 9 , 10 ]. Hyperdense clots are erythrocyte-rich and respond better to mechanical thrombectomy [ 11 , 12 , 13 ]. In contrast, isodense clots are rich in fibrin with increased elasticity and stiffness [ 14 , 15 ] and are associated with unsuccessful reperfusion by mechanical thrombectomy [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have reported that several features on noncontrast computed tomography (NCCT) are indicators of LVO, such as hyperdense arterial signs, 3 , 4 sulcal effacement, 5 and loss of gray-white matter differentiation. 6 While NCCT scans are highly accessible and offer fast acquisition, achieving an accurate diagnosis of LVO from these scans requires expertise in stroke, which is difficult to find in developing countries or hospitals in excessive demand.…”
mentioning
confidence: 99%
“…Previous studies exploring automatic LVO detection using artificial intelligence encountered limitations such as a lack of robust external validation and interpretability in clinical usage. 3 , 4 , 6 To date, there have been a limited number of attempts aimed at extracting handcrafted features that hold clinical relevance to LVO, particularly about ischemic density changes and the presence of clots.…”
mentioning
confidence: 99%